Case Report: BCMA-targeting CAR T-cell therapy induces complete and durable remission in relapsed extramedullary plasmablastic multiple myeloma - Zhou, Lili; Cheng, Paul Ning Man; Mi, Jian-qing (Frontiers in Immunology, 2025)
Plasmablastic multiple myeloma (PBM) is an aggressive multiple myeloma (MM) form, identified by a high risk of recurrence and poor prognosis, with limited effective treatment options. Present study reports a case initially diagnosed with IgG-kappa MM with double-hit genetics. Following induction chemotherapy with bortezomib, doxorubicin and dexamethasone (VAD), and subsequent consolidation therapy with ixazomib, lenalidomide, and dexamethasone, the disease progressed, manifesting as a plasmoblastic tumor in the right pelvic cavity. After two cycles of carfezomib, daratumumab, cyclophosphamide, cisplatin, etoposide and dexamethasone (KD-DECP), the patient achieved partial response. She declined autologous stem cell transplantation (ASCT) and instead received radiotherapy as bridging therapy, followed by B-cell maturation antigen (BCMA)-targeting chimeric antigen receptor (CAR) T-cell therapy with pomalidomide as maintenance therapy. She achieved complete response (CR) at 3 months and has remained disease-free for over 15 months based on the latest follow-up. Although grade 2 cytokine release syndrome (CRS) and other adverse events were observed, they were manageable. BCMA CAR-T cell accompanied with bridging radiotherapy and pomalidomide as maintenance therapy provided a promising therapy treatment for PBM, which is more aggressive and with shorter survival. Further studies are demanded to assess the efficiency and long-term benefits for this challenging subtype.